2004
DOI: 10.1645/ge-202r1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Suis N. Sp. (Apicomplexa: Cryptosporidiidae) in Pigs (Sus Scrofa)

Abstract: Sources of parasite isolatesIsolates were obtained from Cryptosporidium-positive fecal samples from 3-to 5-wk-old pigs (see Table I). Deoxyribonucleic acid extraction, polymerase chain reaction, and sequence analysesOocysts were purified, and deoxyribonucleic acid (DNA) was extract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 26 publications
4
70
1
3
Order By: Relevance
“…In five lambs and in the goat kid sample C. parvum (genotype 2) was identified, based on a high homology (>96%) with previously published sequences, both for the 18SrRNA gene (Ryan et al, 2003) and for the HSP-70 gene (Sulaiman et al, 2000;Ryan et al, 2003). In one lamb the pig genotype of C. parvum or Cryptosporidium suis (Ryan et al, 2004) was identified (homology > 97%). Although there is little information on the genotypes found in sheep and goats, both C. parvum (Chalmers et al, 2002) and C. suis (Ryan et al, 2005) have previously been reported in sheep.…”
Section: Resultsmentioning
confidence: 82%
“…In five lambs and in the goat kid sample C. parvum (genotype 2) was identified, based on a high homology (>96%) with previously published sequences, both for the 18SrRNA gene (Ryan et al, 2003) and for the HSP-70 gene (Sulaiman et al, 2000;Ryan et al, 2003). In one lamb the pig genotype of C. parvum or Cryptosporidium suis (Ryan et al, 2004) was identified (homology > 97%). Although there is little information on the genotypes found in sheep and goats, both C. parvum (Chalmers et al, 2002) and C. suis (Ryan et al, 2005) have previously been reported in sheep.…”
Section: Resultsmentioning
confidence: 82%
“…obs.). Marsupial genotype II has been characterized at 4 loci, the 18S rRNA, internal transcribed spacer 1 (ITS1), Cryptosporidium oocyst wall protein (COWP), and HSP70 loci, and each has confirmed the genetic distinctness of marsupial genotype II from described Cryptosporidium species and genotypes (Power et al, 2004).…”
mentioning
confidence: 92%
“…There are currently 16 species of Cryptosporidium considered as valid; C. serpentis and C. varanii (syn. C. saurophilum) in reptiles; C. molnari and C. scophthalmi in fish; C. baileyi and C. galli in birds; and C. meleagridis in birds and humans; C. suis in pigs; C. muris and C. wrairi in rodents; C. bovis and C. andersoni in cattle; C. felis in cats; C. canis in dogs; C. hominis in humans; and C. parvum in multiple mammalian species, including humans (Fayer et al, 2000(Fayer et al, , 2001Alvarez-Pellitero and Sitja-Bobadilla, 2002;Morgan-Ryan et al, 2002;Ryan et al, 2003Ryan et al, , 2004Alvarez-Pellitero et al, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations